Effect of Ionic Liquid Modification on the ORR Performance and Degradation Mechanism of Trimetallic PtNiMo/C Catalysts - George, Michael; Zhang, Gui-Rong; Schmitt, Nicolai; Brunnengraeber, Kai; Sandbeck, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Etzold, Bastian J.M. (ACS Catalysis, 2019)
Ionic liquids (ILs) modification, following the concept of "solid catalyst with ionic liquid layer (SCILL)", has been demonstrated to be an effective approach to improving both activity and stability of Pt-based catalysts for the oxygen reduction reaction. In this work, the SCILL concept has been applied to a trimetallic PtNiMo/C system, which has been documented recently to be significantly advantageous over the benchmark PtNi-based catalysts for oxygen reduction. To achieve this, two hydrophobic ILs ([BMIM][NTF2] and [MTBD][BETI]) were used to modify PtNiMo/C with four IL-loading amounts between 7 and 38 wt %. We found that the Pt mass activity (@0.9 V) could be improved by up to 50% with [BMIM][NTF2] and even 70% when [MTBD][BETI] is used. Exceeding a specific IL loading amount, however, leads to a mass transport related activity drop. Moreover, it is also disclosed that both ILs can effectively suppress the formation of nonreactive oxygenated species, while at the same time imposing little effect on the electrochemical active surface area. For a deeper understanding of the degradation mechanism of pristine and IL modified PtNiMo/C, we applied identical location transmission electron microscopy and in situ scanning flow cell coupled to inductively coupled plasma mass spectrometry techniques. It is disclosed that the presence of ILs has selectively accelerated the dissolution of Mo and eventually results in a more severe degradation of PtNiMo/C. This shows that future research needs to identify ILs that prevent the Mo dissolution to leverage the potential of the IL modification of PtNiMo catalysts.
CRIS-Team Scopus Importer:2019-09-27
Keywords: electrocatalysis; ionic liquid; metal dissolution; oxygen reduction; PtNiMo catalyst; stability